Lentikat-based biocatalysts : effective tools for inulin hydrolysis - Cattorini, S. (Array, 2009)
Summary: A commercial inulinase preparation from Aspergillus niger was immobilized into polyvinyl alcohol hydrogel lenticular particles (Lentikats®) and into hemispheric-shaped capsules, both based on the use of LentiKat® liquid. The characterization of the resulting biocatalysts, aiming at inulin hydrolysis to fructose, was performed, and the two methods of immobilization were compared. Temperature and pH profiles, as well as kinetic constants were determined, for both free and immobilized enzyme preparations. A broader-shaped curve was observed for the pH-activity profile when immobilized forms were compared to the free form. The apparent KM of inulinase increased roughly 2-fold upon immobilization in either form of the support particles, suggesting diffusion limitations of inulin inside the gel. Long-term operation with immobilized enzymes proved unfeasible above 55 °C, due to the lack of mechanical stability of the supports tested. When the temperature of incubation was lowered to 50 °C, the hemispheric form of the immobilized enzyme displayed considerable long-term operational stability, since it allowed 20 repeated, consecutive batch-mode runs, with a final decay in product yield of 20 %. When inulinase immobilized in Lentikats® particles was used, the final decay in product yield was roughly 70 %